2016
DOI: 10.2139/ssrn.2764872
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Endogeneity and Third-Party Punishment in Social Dilemmas

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The question is whether the effect of introducing piece rate payments on performance is larger 3 These may be the reasons why, despite the wide recognition of the importance of measuring the direct effect of democracy, the identification strategy proposed in Dal Bó, Foster and Putterman (2010) has only been used in a couple of experiments (e.g. Kamei 2016, Chen 2015, Marcin, Robalo and Tausch 2016, and Schories 2017 if that introduction is chosen democratically. In this case, we found that there is no democracy effect: helping to choose the payment scheme of one's group did not affect the number of correct answers provided.…”
Section: Introductionmentioning
confidence: 99%
“…The question is whether the effect of introducing piece rate payments on performance is larger 3 These may be the reasons why, despite the wide recognition of the importance of measuring the direct effect of democracy, the identification strategy proposed in Dal Bó, Foster and Putterman (2010) has only been used in a couple of experiments (e.g. Kamei 2016, Chen 2015, Marcin, Robalo and Tausch 2016, and Schories 2017 if that introduction is chosen democratically. In this case, we found that there is no democracy effect: helping to choose the payment scheme of one's group did not affect the number of correct answers provided.…”
Section: Introductionmentioning
confidence: 99%
“…1 The weak intensity of the third-party punishment has been replicated by subsequent studies (e.g., Carpenter andMatthews 2012, Lergetporer et al 2014). 2 Even when subjects endogenously choose to act as third-party punishers, the level of cooperation declines steadily over time, because the endogenous choice oppositely decreases the intensity of third-party punishment although defectors' responses to punishment increases (Marcin et al 2016). However, in our real life, despite its weak strength seen at the past experimental studies, researchers argue that third-party punishment may substantially help sustain cooperation norms, especially in large-scale societies (e.g., Henrich et al 2006, Marlowe et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Marcin et al (2019) study a three-person public goods game where a fourth player observes the decisions of the three players and can pay to punish the free-riders. They find that subjects in the role of the fourth player punish less when the third-party punishment institution is endogenously chosen by the group than when it is exogenously imposed.…”
mentioning
confidence: 99%